Implementation of Standard Operating Procedures (SOP) on Improving Employee Performance at The Postgraduate Program of Bina Darma University - Helmi, Sulaiman; Annisa, Dian (Indonesian Scientific Publication, 2024)
This study aims to analyze the effect of Standard Operating Procedures (SOP), Standards, Operations, and Procedures on Employee Performance at Bina Darma University Postgraduate Program. The study used a descriptive quantitative method with a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). Data were obtained through questionnaires distributed to 53 employees, covering various job levels. The results of the analysis show that Standards, Operations, and Procedures do not have a significant influence on Employee Performance. However, SOPs have a substantial and positive impact, indicating that implementing well-structured and socialized SOPs can improve employee performance. The findings also identified several obstacles, such as lack of operational efficiency, complex work procedures, and standards that are less relevant to operational needs. This research highlights the importance of SOP optimization in supporting employee performance in the higher education sector. In conclusion, effective implementation of SOPs is a key factor in improving organizational productivity. At the same time, other aspects, such as work standards, operations, and procedures require strengthening through better evaluation and management strategies. This research is limited to the context of Bina Darma University, so further studies are recommended to expand the scope of the subject and add other relevant variables.